Multi-Omics Integration to Reveal the Mechanism of Hepatotoxicity Induced by Dictamnine - Tu, Can; Xu, Ziying; Tian, Lichun; Yu, Zihui; Wang, Tieshang; Guo, Zhaojuan; Zhang, Jingxuan; Wang, Ting (Frontiers in Cell and Developmental Biology, 2021)
Herb-induced liver injury (HILI) has become a great concern worldwide due to the widespread usage of herbal products. Among these products is Dictamni Cortex (DC), a well-known Traditional Chinese Medicine (TCM), widely used to treat chronic dermatosis. Dictamni Cortex has drawn increasing attention because of its hepatotoxicity caused by the hepatotoxic component, dictamnine. However, the potential hepatotoxicity mechanism of dictamnine remains unclear. Therefore, this study aimed to use the multi-omics approach (transcriptomic, metabolomic, and proteomic analyses) to identify genes, metabolites, and proteins expressions associated with dictamnine-induced hepatotoxicity. A study on mice revealed that a high dose of dictamnine significantly increases serum aspartate aminotransferase (AST) activity, total bilirubin (TBIL), and direct bilirubin (DBIL)levels, the relative liver weight and liver/brain weight ratio in female mice (P < 0.05 and P < 0.01), compared to the normal control group. Liver histologic analysis further revealed a high dose of dictamnine on female mice caused hepatocyte vesicular steatosis characterized by hepatocyte microvesicles around the liver lobules. The expressed genes, proteins, and metabolites exhibited strong associations with lipid metabolism disorder and oxidative stress. Dictamnine caused increased oxidative stress and early hepatic apoptosis via up-regulation of glutathione S transferase a1(GSTA1) and Bax/Bcl-2 ratio and down-regulation of the antioxidative enzymes superoxide dismutase (SOD), catalase, and glutathione peroxidase 1 (GPx-1). Besides, the up-regulation of Acyl-CoA synthetase long-chain family member 4 (ACSL4) and down-regulation of acetyl-coa acetyltransferase 1 (ACAT1) and fatty acid binding protein 1 (FABP-1) proteins were linked to lipid metabolism disorder. In summary, dictamnine induces dose-dependent hepatotoxicity in mice, which impairs lipid metabolism and aggravates oxidative stress.